Studying the optimal techniques for removing the organic load from wastewater of hospitals laboratories - Tattan, Abdalrhman (Journal of King Abdulaziz University: Science, 2024)
Hospital wastewater poses a strong threat to human health security as it contains a variety of difficult-to-degrade organic compounds, active pharmaceutical compounds, multiple inorganic pollutants, etc., causing complex pollution in water resources and ecosystems. Aim of this study to treatment wastewater resulting from analysis laboratories in the hospital. waste water was treated using several techniques, including biological treatment using the rotating biological tablets (RBC) method, adsorption with Syrian natural pollutants, coagulation with aluminum sulphate, advanced oxidation with ultrasound, and dual treatment using natural pollutants with ultrasound waves. The effectiveness of organic load removal was determined after each treatment and by applying different treatment conditions. results showed the effectiveness of the treatment methods used, the best way to treat the studied water sample was treatment using natural pollutants with ultrasound waves. Water suitable for irrigation was obtained according to the Syrian standard when adding natural pollutants at a concentration of 1gr per liter of polluted water and applying ultrasound waves at a high frequency. 40kHz for 30 minutes, where the COD value reached 212 mg/l with a removal rate 94%, and the BOD value reached 82 mg/l with a removal rate 87%. Hospital wastewater poses a strong threat to human health security as it contains a variety of difficult-to-degrade organic compounds, active pharmaceutical compounds, multiple inorganic pollutants, etc., causing complex pollution in water resources and ecosystems. Aim of this study to treatment wastewater resulting from analysis laboratories in the hospital. waste water was treated using several techniques, including biological treatment using the rotating biological tablets (RBC) method, adsorption with Syrian natural pollutants, coagulation with aluminum sulphate, advanced oxidation with ultrasound, and dual treatment using natural pollutants with ultrasound waves. The effectiveness of organic load removal was determined after each treatment and by applying different treatment conditions. results showed the effectiveness of the treatment methods used, the best way to treat the studied water sample was treatment using natural pollutants with ultrasound waves. Water suitable for irrigation was obtained according to the Syrian standard when adding natural pollutants at a concentration of 1gr per liter of polluted water and applying ultrasound waves at a high frequency. 40kHz for 30 minutes, where the COD value reached 212 mg/l with a removal rate 94%, and the BOD value reached 82 mg/l with a removal rate 87%.